Analysis of Implementation “Proactive Recruitment” in NCO POLRI Recruitment and Selection at Regional Police of the Bangka Belitung Islands, 2021 - Yudha Prakoso; Vishnu Juwono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Human resource management in the National Police aims to maximize the role and function of human resources (HR) in each work unit, so that every HR within the Polri organization has the same motivation and goals. aligned with organizational goals. One form of HR management carried out by the National Police is to organize personnel recruitment, the implementation of this recruitment as an effort to build a superior Polri HR posture. From several aspects of Polri's HR management, the process of recruitment and selection of personnel is one aspect that plays an important role in creating a superior and partnership able to excel and innovate. This aspect is in line with the vision and mission of the National Police Chief outlined in the National Police Chief's Priority Program with reference to the vision and mission of the President of the Republic of Indonesia, one of which is to create superior human resources (HR). Recruitment with a proactive model can overcome the shortcomings of the classic recruitment model, where in proactive recruitment the talents and talents of each candidate can be identified. As one of the National Police's efforts to create superior Human Resources (HR), a proactive recruitment was held in the 2021 National Police Officer recruitment selection. This research was conducted at Regional Police of the Bangka Belitung Islands, it was qualitative research which used a post-positivism approach. Data collection techniques used were interviews, observations, and documentations. The interviews were conducted on 15 respondents.